The Contribution of Online Assistance for Student Learning Outcome During Distance Learning to The Technical Drawing Subject at Public Vocational High School 6 (PVHS 6) in Bandung - Adila, Mutiara; Permana, Asep Yudi; Yosita, Lucy (Journal of Architectural Research and Education, 2021)
Abstract – The Minister of Education and Culture of the Republic of Indonesia has issued a Circular Letter Number 4 of 2020 concerning the Implementation of Education Policy in the Emergency Period of Coronavirus Disease (Covid-19) that teaching and learning activities are carried out from home. Learning in distance is a solution from the government to execute learning activities then they can continue to run during the pandemic period, by utilizing the online media. Distance learning also occurs in productive subjects in vocational high schools, such as technical drawing subject. The technical drawing subject during distance learning is limited by time, even though this technical drawing subject requires a very long time because it requires quite high accuracy. Thus online assistance became one of the solutions to guiding students outside the technical drawing hour’s lesson during distance learning through online media such as computer, television, radio, telephone, internet, video, etc. Assistance usually with face-to-face, one of its aims is helping the learning process of students who are having difficulty of understanding the material and build students to achieve the learning goals, but during distance learning assistance is carried out online. The obstacles found in the online assistance, they are the students’ devices, teachers’ communication with students, teachers are difficult to drawing checking, and students are difficult to understand the material. The method used in this research is a quantitative descriptive method with a number of samples is 46 involve the class of first grade students in Modeling and Building Information Design Program (MBID) at PVHS 6 in Bandung. Data collection techniques use two ways, they are questionnaire techniques with a 39 number of questions grains on online assistance variables and documentation techniques on learning outcomes by referring to student’s value on the task of the technical drawing subject. Before data analysis, an instrument test was using the validity and reliability test. Then, perform the analysis of the level of respondents to find out the general description of the variables. Furthermore, data analysis was carried out by the normality test, correlation test, regression test, and hypothesis test. The results of the research obtained were known that the achievement level of online assistance with fairly good category. Also the achievement level of students learning outcome with fairly good category. While the acquisition of online assistance contribution to learning outcomes is 9% by determination analysis and the correlation coefficient is equal to 0.300 which means the relationship category is weak. Therefore, the hypothesis (Ha) is accepted, there are positive contributions between online assistance to learning outcomes.Keywords – Online Assistance, Technical Drawing, Learning Outcome, Distance Learning.